E-Module Based on Content Differentiation in Civics Education for Grade 10 Senior High School - Wulan Dari, Tri Ayu; Alfiandra; Safitri, Sani (Universitas Pendidikan Ganesha, 2025)
This study aims to solve learning problems with E-Modules oriented to Differentiated Content Learning in PPKn subjects that are valid, practical, and have a potential effect on students' learning motivation. The type of research used in this study is Research & Development (R&D) with the ADDIE Model. The subjects of the study were ten grades students. The validity test of the E-Modules oriented to Differentiated Content Learning was carried out by three experts, namely media experts, material experts, and language experts. The results of the media validation obtained a percentage of 90.74% including the very valid category, material validation, namely 84.52% including the very valid category, and language validation 73.21% including the valid category. The results of the practicality test, at the one-to-one stage obtained a percentage of 90% and the small group stage obtained a percentage of 90% including the very practical category. Furthermore, the results of the potential effect test at the field test stage from the observation results obtained a percentage of 88% including the very good category. Based on these results, it can be concluded that the E-Module oriented towards Differentiated Content Learning is stated to be valid, practical, and has a potential effect on students' learning motivation.